MAYO CLINIC COLLEGE OF MEDICINE AND SCIENCE: past, present and future - Azizova, Feruza; Okhunov, Alisher (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Mayo Clinic is a private American academic medical center focused on integrated healthcare, education, and research. It maintains three major campuses in Rochester, Minnesota; Jacksonville, Florida; and Phoenix/Scottsdale, Arizona. Mayo Clinic employs over 7,300 physicians and scientists, along with another 66,000 administrative and allied health staff. The practice specializes in treating difficult cases through tertiary care and destination medicine. It is home to the top 15 ranked Mayo Clinic Alix School of Medicine in addition to many of the highest regarded residency education programs in the United States. It spends over 660 million a year on research and has more than 3,000 full-time research personnel. William Worrall Mayo settled his family in Rochester in 1864 and opened a sole proprietorship medical practice that evolved under his sons, Will and Charlie Mayo, along with practice partners Stinchfield, Graham, Plummer, Millet, Judd, and Balfour, into Mayo Clinic. Today, in addition to the hospital at Rochester, Mayo Clinic has major campuses in Arizona and Florida. Most recently, in 2020, the Mayo Clinic bought a facility in central London, UK. The Mayo Clinic Health System also operates affiliated facilities throughout Minnesota, Wisconsin, and Iowa. Mayo Clinic has been ranked number one in the United States for seven consecutive years in U.S. News & World Report’s Best Hospitals Honor Roll, maintaining a position at or near the top for more than 35 years. It has been on the list of "100 Best Companies to Work For" published by Fortune magazine for fourteen consecutive years and has continued to achieve this ranking through 2017. Drawing in patients from around the globe, Mayo Clinic performs near the highest number of transplants in the country, including both solid organ and hematologic transplantation.